A benzothiazole-based "on-off" fluorescence probe for the specific detection of Cu2+ and its application in solution and living cells. (February 2023) - Zhao, Li-xia; Chen, Kun-yu; Xie, Kai-bo; Hu, Jia-jun; Deng, Meng-yu; Zou, Yue-li; Gao, Shuang; Fu, Ying; Ye, Fei
Abstract: In this paper, a novel fluorescent probe HBT-H based on benzothiazole has been designed and synthesized. The probe has excellent selectivity and can be used for specific detection of Cu 2+ . Under 360 nm UV excitation, the probe HBT-H itself has a fluorescence emission peak at 487 nm, emitting cyan blue fluorescence, fluorescence quenching after added Cu 2+ . The detection limit of Cu 2+ recognition by HBT-H probe was calculated as 3.08 × 10 −7 M. According to Job's plot and high resolution mass spectrometry, the complexation ratio of HBT-H to Cu 2+ was 2:1. The sensor mechanism was confirmed as excited intramolecular proton transfer (ESIPT). Surprisingly, the probe HBT-H system responded well to pH, showing green fluorescence under acidic conditions and cyan blue fluorescence under alkaline conditions. In addition, the probe HBT-H has excellent membrane permeability and low cytotoxicity, which could not only detect Cu 2+ in actual water samples, but also recognize Cu 2+ in human breast cancer cells (MCF-7). Graphical abstract: Image 1 Highlights: The probe could selectively detect Cu 2+ from solutions or water samples. The detection limit of Cu 2+ with this probe was as low as 3.08 × 10 −7 M. The probe could be used to judge the acid-base properties colorimetrically. The probe was successfully applied to the imaging of human breast cancer cells.